STUDY OF THE MECHANISM OF CHANGES IN THE HEART RATE OF PAROXYSMAL TACHYCARDIA - Umarov Sherali Burhonova Nigora Aliyev Alisher Maxamadiyev Ròzimurod (Journal of Science in Medicine and Life, 2024)
Paroxysmal tachycardia is one of the types of arrhythmia manifested by heart attacks with an increase in heart rate of 140-220 beats per minute or more. A fast heartbeat is caused by impulses that replace the normal sinus rhythm. Attacks usually begin and end suddenly, vary in duration, and maintain a regular rhythm (in most cases). Pathological impulses can appear in the atrioventricular node, atrium and ventricles.